Remdesivir for Treating Non-Hospitalized Patients with COVID-19 - Ahmed Shah, Zahoor; Shakoor, Abdul; Bhatti, Hammad-Ur-Rehman (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To examine the effect of remdesivir for treating non-hospitalized patients with COVID-19. Study design: Retrospective study Place and duration of study: Department of Medicine, Bolan Medical College, Quetta from 1st April 2021 to 30th September 2021. Methodology: One hundred patients were enrolled and divided into group A and group B within the age of 24-70 years. Group A was receiving remdesivir while group B is not receiving remdesivir. The clinical variables, BMI, comorbidities, duration of disease severity and viral load were determined. RT-PCR was conducted to determine viral load. Results: The mean age of study participants was 50±15 years with greater number of males. Diabetes was the major comorbidity. The time duration was decreased in group A upto 5 days and 8 days in group B. The viral load was decreased by mean value 6.32±1.76 to 6.2±1.78 in group B then group A respectively. Conclusion: Remdesivir is effective in COVID-19 treatment.